Relationship Between 24-Hour Ambulatory Central Systolic Blood Pressure and Left Ventricular Mass - Thomas Weber; Siegfried Wassertheurer; Arno Schmidt‐Trucksäss; Enrique Rodilla; Cornelia Ablasser; Piotr Jankowski; María Lorenza Muiesan; Cristina Giannattasio; Claudia Mang; Ian B. Wilkinson; Joerg Kellermair; Bernhard Hametner; et al. (2017)
We investigated the relationship between left ventricular mass and brachial office as well as brachial and central ambulatory systolic blood pressure in 7 European centers. Central systolic pressure was measured with a validated oscillometric device, using a transfer function, and mean/diastolic pressure calibration. M-mode images were obtained by echocardiography, and left ventricular mass was determined by one single reader blinded to blood pressure. We studied 289 participants (137 women) free from antihypertensive drugs (mean age: 50.8 years). Mean office blood pressure was 145/88 mm Hg and mean brachial and central ambulatory systolic pressures were 127 and 128 mm Hg, respectively. Mean left ventricular mass was 93.3 kg/m2, and 25.6% had left ventricular hypertrophy. The correlation coefficient between left ventricular mass and brachial office, brachial ambulatory, and central ambulatory systolic pressure was 0.29, 0.41, and 0.47, respectively (P=0.003 for comparison between brachial office and central ambulatory systolic pressure and 0.32 for comparison between brachial and central ambulatory systolic pressure). The results were consistent for men and women, and young and old participants. The areas under the curve for prediction of left ventricular hypertrophy were 0.618, 0.635, and 0.666 for brachial office, brachial, and central ambulatory systolic pressure, respectively (P=0.03 for comparison between brachial and central ambulatory systolic pressure). In younger participants, central ambulatory systolic pressure was superior to both other measurements. Central ambulatory systolic pressure, measured with an oscillometric cuff, shows a strong trend toward a closer association with left ventricular mass and hypertrophy than brachial office/ambulatory systolic pressure.URL: https://www.clinicaltrials.gov. Unique identifier: NCT01278732.